Effect of 2% Chlorhexidine Gel Medicament on Push-out Bond Strength of Epoxy Resin and Bioceramic Sealers in teeth extracted from Diabetics: An In-vitro Study - Naveena Thalabhakthula; CH Ram Sunil; Ram Chowdary Basam; Sayesh Vemuri; Roopa Devi Garlapati; Sai Tejaswi Gorre (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Diabetes Mellitus (DM) impairs healing, immune function and dentin metabolism, potentially affecting adhesion. Chlorhexidine (CHX) gel is widely used as an intracanal medicament due to its sustained antimicrobial action; however, its influence on sealer bonding in diabetes-altered dentin is unclear. AH Plus® and BioRoot Root Canal Sealer (RCS) sealers are commonly used, yet their adhesion following 2% CHX application requires evaluation. Aim: To evaluate the effect of 2% CHX gel on the Push-Out Bond Strength (POBS) of AH Plus® and BioRoot RCS in teeth from diabetics. Materials and Methods: This in-vitro study was conducted at the Department of Conservative Dentistry and Endodontics, Sibar Institute of Dental Sciences, Guntur, Andhra Pradesh, India. The study duration was three months, from June 2024 to August 2024. A total of 52 single-rooted teeth were prepared up to size 35/06 using Sodium Hypochlorite (NaOCl), sonic activation and Ethylenediaminetetraacetic Acid (EDTA). Specimens were divided into two groups: without 2% CHX (Group-1) and with 2% CHX (Group-2) gel applied for two weeks, followed by obturation using AH Plus® and BioRoot RCS. After two weeks, 2-mm mid-root slices were subjected to POBS testing and bond failure mode analysis. Results: One-way Analysis of Variance (ANOVA) showed a significant difference in POBS among the groups (F value 9.36, p-value